2009
DOI: 10.4088/jcp.08m04905
|View full text |Cite
|
Sign up to set email alerts
|

Lurasidone in the Treatment of Acute Schizophrenia

Abstract: (ClinicalTrials.gov) Identifier: NCT00088634.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
138
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 183 publications
(172 citation statements)
references
References 0 publications
13
138
1
1
Order By: Relevance
“…Two previously reported phase II studies demonstrated significantly greater efficacy for lurasidone compared with placebo [Nakamura et al 2009;Ogasa et al 2013].…”
mentioning
confidence: 93%
“…Two previously reported phase II studies demonstrated significantly greater efficacy for lurasidone compared with placebo [Nakamura et al 2009;Ogasa et al 2013].…”
mentioning
confidence: 93%
“…[1][2][3][4][5] However, efficacy was not consistently shown for each dose and a dose-response relationship was not evident in the trials. For example, in a study of lurasidone 40 mg, 80 mg and 120 mg, only the 80 mg dose had a statistically significant effect over placebo.…”
Section: New Drugsmentioning
confidence: 93%
“…4 Discontinuation rates were very high in some of the trials (28-65%). [1][2][3][4][5] Lack of efficacy and withdrawal of consent were the most common reasons for stopping treatment.…”
Section: New Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lurasidone has demonstrated efficacy in acute and long-term treatment of schizophrenia, [24][25][26] as well as in treatment of bipolar depression, both as monotherapy and as an adjunctive therapy with lithium or valproate. 27,28 The purpose of the present post-hoc analysis was to assess the efficacy of lurasidone in treating MDD patients with mixed features presenting with irritability.…”
Section: Introductionmentioning
confidence: 99%